Changes in Implementation of Two Evidence‐Based Psychotherapies for PTSD in VA Residential Treatment Programs: A National Investigation. Issue 2 (25th March 2014) - Cook, Joan M.; Dinnen, Stephanie; Thompson, Richard; Simiola, Vanessa; Schnurr, Paula P.
Abstract: There has been little investigation of the natural course of evidence‐based treatments (EBTs) over time following the draw‐down of initial implementation efforts. Thus, we undertook qualitative interviews with the providers at 38 U.S. Department of Veterans Affairs' residential treatment programs for posttraumatic stress disorder (PTSD) to understand implementation and adaptation of 2 EBTs, prolonged exposure (PE), and cognitive processing therapy (CPT), at 2 time points over a 4‐year period. The number of providers trained in the therapies and level of training improved over time. At baseline, of the 179 providers eligible per VA training requirements, 65 (36.4%) had received VA training in PE and 111 (62.0%) in CPT with 17 (9.5%) completing case consultation or becoming national trainers in both PE and CPT. By follow‐up, of the increased number of 190 eligible providers, 87 (45.8%) had received VA training in PE and 135 (71.1%) in CPT, with 69 (36.3%) and 81 (42.6%) achieving certification, respectively. Twenty‐two programs (57.9%) reported no change in PE use between baseline and follow‐up, whereas 16 (42.1%) reported an increase. Twenty‐four (63.2%) programs reported no change in their use of CPT between baseline and follow‐up, 12 (31.6%) programs experienced an increase, and 2 (5.2%) programs experienced a decrease in use. A significant number of providers indicated that they made modifications to the manuals (e.g., tailoring, lengthening). Reasons for adaptations are discussed. The need to dedicate time and resources toward the implementation of EBTs is noted.